Synthesis of nanostructured Ni(Co)/C/SiO2 composites from cellulose derivatives through sol-gel approach - Baldaia, Joana (My University, 2012)
Carbon nanostructured composites have gained a lot of interest, since they have unique chemical, physical, magnetic and mechanical properties. These materials have potential for a wide range of application as energy storage, catalysis, supercapacitors, sensors, drug delivery, ion exchange and separation processes. The aim of this project was the synthesis of Ni(Co)/C/SiO2 composites by sol-gel approach using cellulose acetate and hydroxypropyl cellulose as a carbon precursors and TEOS as silica precursor. These polymers were chosen as carbon precursors because of their renewability and low cost. Synthesized materials were investigated with low-temperature nitrogen sorption, scanning electron microscopy (SEM),x-ray diffraction (XRD) and thermal gravimetric analysis (TGA). Micro-and mesoporous Ni(Co)/C/SiO2 composites with the specific surface area up to 346 m2/g were synthesized by carbonization precursor containing xerogels. Presence of metallic Ni and Co was proven with XRD. Our study showed that the structure and properties of the nanocomposites synthesized are influenced by precursor and type of metal salt used. The using of cellulose acetate and cobalt bromide made it possible to prepare silica/carbon materials with surface area values up 346 m2 g-1. Received results could be explained with complex interactions between Ni(II) or Co(II) salt, precursor and silica in formed gels.
Keywords: Kemi; Hållbar utveckling; Materialteknik; Miljöbioteknik; Materialvetenskap; Nanoteknik; Nanovetenskap och nanoteknik; Produktion; Chemical Sciences; Sustainable Development; Materials Engineering; Environmental Biotechnology; Materials Science; Nano Technology; Nanoscience & Nanotechnology; Production